Gastric Xanthomatosis Secondary to Lipoprotein X in Primary Biliary Cholangitis. (April 2022) - Petrie, Erin; Hoppmann, Nicholas A.; Wilcox, C. Mel; Al Diffalha, Sameer; Gray, Meagan E.
Primary biliary cholangitis (PBC) is a rare autoimmune disease characterized by intralobular bile duct destruction. Patients typically present with generalized symptoms including fatigue and pruritis, and less commonly, manifestations of lipid deposition including xanthomas and xanthelasmas. We report a case of a 31-year-old female with PBC-associated cirrhosis who had cutaneous xanthelasmas and diffuse gastric xanthomas secondary to hyperlipidemia and lipoprotein X that completely resolved following liver transplantation. While gastric xanthomas have been reported in patients with PBC previously, to our knowledge, this is the first case report of diffuse gastric xanthomas secondary to PBC reported to resolve following liver transplantation, suggesting that liver transplantation is curative for gastric xanthomatosis in patients with PBC-related cirrhosis.